Public Communication Management of Kodim 0201/Medan in Disseminating the Medan City Covid-19 Vaccine Program - Budianto H. Damanik (Budapest International Research and Critics University, 2022)
The Covid-19 vaccination is one of the Government's ways in tackling the current pandemic, this requires good communication and education between the Government and the public regarding the Covid-19 vaccination, so that there is no confusion about the news regarding the vaccination program so that good cooperation is established between the parties. Government and society to make the Covid-19 vaccination program a success. This study aims to explain the role of Kodim 0201 in disseminating the Covid-19 vaccination program to the public. By using the Instrumental Model of Persuation theory. The researcher here uses a qualitative method with a descriptive study, where this study aims to examine a phenomenon and describe how Kodim 0201 is in the socialization process through the results of in-depth interviews with resource persons taken based on purposive sampling technique. The community response to this vaccination program was very good and the community was very enthusiastic about the existing vaccination program, and participated in carrying out the vaccination program. From the results obtained in this study reported from the Medan city government, there were 1.515.897 people and above who had been vaccinated due to the support role of the 0201 Military Command which took part in helping the Medan city government socialize the Covid-19 Vaccine program.